Christopher Boone and the curious incident of the dog in the night-time : a detective story triggering reflection on how autism helps people acknowledge the importance of pursuing different goal paths for the same objective - Chamorro Gutiérrez, Daniela (Universidad de Santiago de Chile, 2021)
Integrantes: Daniela Chamorro Gutiérrez, Diego Espinoza Lazo, Romina Fuentes Hernández, Valeria González Acevedo
Keywords: Haddon, Mark. The curious incident of the dog in the night-time; Autismo infantil - Literatura infantil; Literatura juvenil estadounidense